Health profile of residents of retirement villages in Auckland, New Zealand: findings from a cross-sectional survey with health assessment - Kathy Peri; Michal Boyd; Martin J Connolly; Joanna B Broad; Dale Bramley; Zhenqiang Wu; Katherine Bloomfield; Joanna Hikaka; Annie Tatton; Cheryl Calvert; Ann-Marie Higgins (BMJ Open)
Objectives Retirement villages (RV) have expanded rapidly, now housing perhaps one in eight people aged 75+ years in New Zealand. Health service initiatives might better support residents and offer cost advantages, but little is known of resident demographics, health status or needs. This study describes village residents—their demographics, socio-behavioural and health status—noting differences between participants who volunteered and those who were sampled.Design Cross-sectional study of village residents. The cohort formed will also be used for a longitudinal study and a randomised controlled trial. Village managers (sometimes after consulting residents) decided if representative sampling could be undertaken in each village. Where sampling was not approved, volunteers were sought.Setting 33 RV were included from a total of 65 villages in Auckland, New Zealand.Participants Residents (n=578) were recruited either by sampling (n=217) or as volunteers (n=361) during 2016–2018. Each completed a survey and an International Resident Assessment Instrument (interRAI) health needs assessment with a gerontology nurse specialist.Results Median age of residents was 82 years, 158 (27%) were men; 61% lived alone. Downsizing (77%), less stress (63%) and access to healthcare assistance (61%) were most common reasons for entry. During the 2 weeks prior to survey, 34% received home supports and 10% personal care. Hypertension, heart disease, arthritis and pain were reported by over 40%. Most common unmet needs related to managing cardiorespiratory symptoms (50%) and pain (48%). Volunteers and sampled residents differed significantly, mainly in socio-behavioural respects.Conclusions Common conditions including hypertension, arthritis and atrial fibrillation, are recorded in interRAI as text, and thus overlooked in interRAI reports. Levels of unmet need indicate opportunities to improve health services to better manage chronic conditions. Healthcare service providers and village operators could cooperate to design and test service initiatives that better meet residents’ needs and offer cost benefits.Trial registration number ACTRN12616000685415.